(untitled) (CIPEEX, 2025)
INTRODUCTION: Sarcopenia is a multifactorial condition closely related to the aging process, being characterized by progressive and involuntary loss of muscle mass and strength. This syndrome results from a set of interconnected factors, such as sedentary lifestyle, inadequate nutritional intake, oxidative stress and hormonal changes. Its effects significantly compromise the functional autonomy of the elderly, making it difficult to perform daily activities and increasing the risk of dependence, in addition to the need for prolonged care. OBJECTIVE: In this context, this work aims to analyze the influence of hormonal changes on the development of sarcopenia and its impacts on the functionality and quality of life of the elderly. METHODOLOGY: This is an integrative literature review, the search followed the PICo strategy and was carried out on bases such as PubMed, SciELO and VHL, with rigorous inclusion and exclusion criteria. Of the 282 results, only 5 met the study criteria. RESULTS: The analyzed studies show that sarcopenia is directly related to hormonal changes, such as the reduction of testosterone and IGF-1, in addition to the increase in inflammatory cytokines such as IL-6, which ends up resulting in the intensification of muscle degradation. As a consequence, there is a significant loss in the functionality and autonomy of the elderly, compromising basic daily activities. In addition, there is a negative impact on quality of life, especially on physical aspects and general health status. Therefore, the authors converge by recommending integrated interventions, such as resistance exercise, nutritional supplementation and, when necessary, hormonal therapies, as effective strategies for the prevention and treatment of sarcopenia. CONCLUSION: It is concluded that hormonal changes exert a significant influence on the development and progression of sarcopenia, directly compromising the functionality and quality of life of the elderly. In this sense, integrated interventions - such as physical exercise, nutritional supplementation and hormonal therapies - are fundamental for the prevention and effective management of this condition in the aging process.